A revision of the click beetle genus Ctenoplus Candèze, 1863 (Coleoptera: Elateridae, Synaptina) - Fuller, E.; Platia, G. (Zootaxa, 2006)
The Oriental Region click beetle genus Ctenoplus Candèze is redefined based on the structure of the head capsule and female genitalia. Of the 23 species recognized, 16 are described as new: C. sumatrensis n. sp., C. sanguinolentoides n. sp., C. indicus n. sp., C. pseudocollaris n. sp., C. neosiamensis n. sp., C. siamensis n. sp., C. rufoantennatus n. sp., C. divergens n. sp., C. gigas n. sp., C. balli n. sp., C. girardianus n. sp., C. cateianus n. sp., C. deceptus n. sp., C. dorsalis n. sp., C. alutaceus n. sp. and C. semialutaceus n. sp.. Silesis castaneus Fleutiaux, S. tonkinensis Fleutiaux and S. coomani Fleutiaux are transferred to Ctenoplus. The following synonymies are proposed: C. nigripennis Schwarz = C. nitidipennis Schwarz; S. tonkinensis, S. coomani and C. topali Ohira = C. coomani Fleutiaux. Lectotypes are designated for C. sanguinolentus (Candèze), C. nitidipennis, C. nigripennis, C. collaris Candèze, C. coomani, S. coomani, C. brunneus Fleutiaux and S. fulvus Fleutiaux. Silesis coomani is renamed C. confusus Platia to remove a subsequent homonymy. Silesis fulvus, which had been included in Ctenoplus is returned to Silesis. Difficulties with the diagnosis of Silesis (s.l.) are discussed.